MENINGKATKAN KEMAMPUAN BERBAHASA LISAN ANAK MELALUI MEDIA CERITA BERGAMBAR - Bujuna Alhaddad (Universitas Khairun, 2015)
Language is a tool of communication that is very important in a childâ€™s life. Based on the growth and development of childrenâ€™s language product also increased in quantity and complexity.Â That is why the researcher offers story telling media to improve children language skill. Story telling provides experiences and informations between teacher and early childhood that can be delivered directly or indirectly. This research applied classroom action research with two cycles. The subjects of the research are kindergarten students in Weda consist of 13 students. From this research, it showed that the kindergarten students language skill was improved after the implementation of story telling media in the classroom. It can be seen in the score for each test passing the criteria.Key word: language, storytelling, media